The Psychological Characteristics of Developing Healthy Thinking In Students - Utkurovna , Atakhanova Sayyora (Jurnal Psikologi, 2024)
This article explores the challenges related to the harmonious development of students' independent and healthy thinking. It emphasizes the importance of fostering independence in decision-making and responsibility, as well as the formation of personal ideas and thoughts. The article also highlights the psychological aspects involved in cultivating healthy thinking among students.